2003
DOI: 10.1039/b307498f
|View full text |Cite
|
Sign up to set email alerts
|

N2O5 hydrolysis on sub-micron organic aerosols: the effect of relative humidity, particle phase, and particle size

Abstract: Measurements of the reactive uptake coefficient for N 2 O 5 hydrolysis, g m , on sub-micron organic aerosols were performed in an entrained aerosol flow tube as a function of relative humidity (RH), aerosol phase, N 2 O 5 partial pressure, and mean aerosol size. Aerosol phase and relative humidity were determined simultaneously, and chemical ionization mass spectrometry was used to detect the decay rate of N 2 O 5 in the presence of malonic acid or azelaic acid aerosol. The g m on solid malonic acid was determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
366
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(403 citation statements)
references
References 38 publications
35
366
1
1
Order By: Relevance
“…The observed particle-phase ON group hydrolysis rate (Figure 5b) is consistent with the phase transition of SOA from solid to semisolid/liquid particles: The hydrolysis rate was ∼0 and 4 day −1 (corresponding to a lifetime of 6 h) for RH < 20% and > 40% experiments, respectively. The pronounced increase of hydrolysis rate at 40% RH also agrees with the hydrolysis loss rate of N 2 O 5 on organic particles, which is dependent on water concentration when RH < 50% and appears to be independent of water when RH is greater than 50% (Thornton et al 2003).…”
Section: Fig 3 Time-dependence Of (A) Rh (B) Temperature (C) Tmbsupporting
confidence: 69%
“…The observed particle-phase ON group hydrolysis rate (Figure 5b) is consistent with the phase transition of SOA from solid to semisolid/liquid particles: The hydrolysis rate was ∼0 and 4 day −1 (corresponding to a lifetime of 6 h) for RH < 20% and > 40% experiments, respectively. The pronounced increase of hydrolysis rate at 40% RH also agrees with the hydrolysis loss rate of N 2 O 5 on organic particles, which is dependent on water concentration when RH < 50% and appears to be independent of water when RH is greater than 50% (Thornton et al 2003).…”
Section: Fig 3 Time-dependence Of (A) Rh (B) Temperature (C) Tmbsupporting
confidence: 69%
“…Note that γ N 2 O 5 values appeared to increase with rising relative humidity, which was also observed at other sites (X. Thornton et al, 2003). For example, γ N 2 O 5 values increased from 0.019 to 0.090 when RH increased from 21.1 % to 63.6 %.…”
Section: N 2 O 5 Uptake Coefficient and Clno 2 Production Yieldsupporting
confidence: 49%
“…However, the γ N 2 O 5 determined in our campaign was 1-2 or- ders of magnitude higher than obtained in the laboratory (Thornton et al, 2003) and also much higher than those in Hong Kong and Germany (Brown et al, 2016b;Phillips et al, 2016). We also found that the parameterized γ N 2 O 5 values (0.0014-0.012) determined from Eq.…”
Section: N 2 O 5 Uptake Coefficient and Clno 2 Production Yieldsupporting
confidence: 48%
See 1 more Smart Citation
“…For instance, the total gas-to-particle transfer rate of N 2 O 5 K N 2 O 5 is calculated as the sum of the specific K N 2 O 5 ,i x as follows: [29] We implemented the reactions of HO 2 , NO 2 , NO 3 on wet aerosol particles (e.g., all the soluble modes (NS, KS, AS, and CS) in the model, independently of their composition) with the uptake coefficients of 0.2, 10 À4 and 10 À3 , respectively, following Jacob [2000]. The uptake of N 2 O 5 on aerosol particles follows Evans and Jacob [2005] and Liao and Seinfeld [2005], i.e., different coefficients are used for sulfate [Kane et al, 2001;Hallquist et al, 2003], organic carbon [Thornton et al, 2003], black carbon [Sander et al, 2003], sea salt [Atkinson et al, 2004], and mineral dust [Bauer et al, 2004]. The O 3 uptake coefficient on mineral dust is set to 10 À5 following Bauer et al [2004].…”
Section: Heterogeneous Chemistrymentioning
confidence: 99%